Genetic progress in oat breeding in Southern Brazil - Neto, José F. Barbosa; Matiello, Rodrigo R.; Carvalho, Fernando I. F. de; Oliveira, João M. S.; Pegoraro, Diego G.; Schneider, Fernanda; Sordi, Maria Elena B.; Vacaro, Elton (Pesquisa Agropecuaria Brasileira, 2000)
The oat (Avena sativa L.) cultivars cultivated in Southern Brazil up to the beginning of the 80's were introduced from Uruguay and Argentina. They presented adaptation problems to the new environment. Starting from the 70's, oat breeding programs began to produce their own segregant populations. These programs already released 35 cultivars. Aiming to estimate the genetic progress in oat breeding programs from southern Brazil, an experiment with 15 cultivars released in different times was conducted in two locations using four different cultural practices. The results indicated linear genetic progress for days to flowering, grain yield, grain weight and test weight. The non significance of quadratic effects suggested the possibility of additional gains through selection of new genotypes. The oat breeding programs in southern Brazil have been efficient in producing new cultivars with higher grain yield, good grain quality, and with superior agronomic traits. However, a maximum breeding plateau was not reached for this species.